A Guide to Delineate the Logic of Neurovascular Signaling in the Brain - Kleinfeld, David; Blinder, Pablo; Drew, Patrick J.; Driscoll, Jonathan D.; Muller, Arnaud; Tsai, Philbert S.; Shih, Andy Y. (Frontiers in Neuroenergetics, 2011)
The neurovascular system may be viewed as a distributed nervous system within the brain. It transforms local neuronal activity into a change in the tone of smooth muscle that lines the walls of arterioles and microvessels. We review the current state of neurovascular coupling, with an emphasis on signaling molecules that convey information from neurons to neighboring vessels. At the level of neocortex, this coupling is mediated by: (i) a likely direct interaction with inhibitory neurons, (ii) indirect interaction, via astrocytes, with excitatory neurons, and (iii) fiber tracts from subcortical layers. Substantial evidence shows that control involves competition between signals that promote vasoconstriction versus vasodilation. Consistent with this picture is evidence that, under certain circumstances, increased neuronal activity can lead to vasoconstriction rather than vasodilation. This confounds naïve interpretations of functional brain images. We discuss experimental approaches to detect signaling molecules in vivo with the goal of formulating an empirical basis for the observed logic of neurovascular control.